STUDI PEMETAAN SISTEMATIS : UKM PARAWISATA - ahmad hadi fauzi (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
This article is preliminary research to explore the results of studies conducted in the field of Tourism SMEs by using systematic mapping studies (SMS) or systematic monitoring studies. The purpose of this Mapping is to discuss any SMEs Tourism topics that are reviewing. This research uses a qualitative method using a study library. The search was conducted on the Scopus database of 36 articles in the 2002-2019 publication which were published in the form of scientific journals included in the inclusion criteria. The results of this SMS can provide an overview of opportunities to explore new topics in SMEs Tourism or exploit existing topics about the biggest focus of ICT, tourism management, innovation, for the locus of Small Business Travel Agents / tour operators / Guides, Guides, Hotels and Motels, Cafes and restaurants, Adventure Tourism, Recreation and Camping. As for the trends of countries and continents which often plagiarize the UK and European continents.